The Review of Recitation Ways Correlated to Hafsa in The Context of Maturidi's Interpretation - Saylan, Nesrisah (Dinbilimleri Akad Arastirma Merkezi, 2020)
Hafsa was one of the Prophet's wives and the daughter of Umar who was the second of four great caliphs. Hafsa was one of the precious companions who knew the literacy in that period. Moreover, one of the greatest feature of Hafsa is that she was chosen for an important duty such that The Qur'an's verses which were collected in Abu Bakir's period were delivered to Umar after Abu Bakir's death and then, they were delivered to Hafsa. Hafsa was the person who knew and understood the Qur'an best also famous with The Qur'an's memorization and recitation among other companions; thereby had an important position in the recitation science. The fact that she has her own copy of the Quran and own way of recitation, as stated in the sources, supports this view. So Hafsa's way of recitation written in the literature and the aforementioned ways are used in the interpretation and gloss of verse as they are evaluated in many aspects. One of the glossators who included Hafsa's recitation ways in those interpretations in the most extensive way is Maturidi. One of the reasons which inclined us to such a study is that Maturidi mostly included Hafsa's way of recitation in his interpretation. So Maturidi used Hafsa's way of recitation in the context of recitation-interpretation relationship such as interpretation of verse in a different way, explanation of word's meaning, elimination of closure in the verse, support of views mentioned about the verse.
Keywords: Qur'an; Interpretation; Recitation; Hafsa; Maturidi